A urbanização afeta negativamente a diversidade de besouros: uma revisão integrativa - Jéssica Aparecida Alves Lima (2021)
Urbanization is considered one of the main threats to biodiversity at a global level. The conversion of natural areas to urban areas can lead to species loss leading to changes in the ecological processes that regulate the functioning of ecosystems and the provision of ecosystem services. Although many studies demonstrate a reduction in the number of species in urban areas, the effects of urbanization are not always negative, since different urban landscapes can provide resources, such as shelter and food for some species. In order to understand the impacts of changes caused by the development of cities on the patterns of structure and diversity of beetle communities, we carried out an integrative review. Initially, we address the overview of published studies on insects of the Coleoptera order in urban areas. After, through a meta analysis, we test the hypothesis that urbanization negatively affects the richness and diversity of beetles in urban areas at the local and landscape scale. Overall, we found an increase in the number of studies involving beetles in urban areas over the years and a greater concentration of studies being carried out in the temperate region. Furthermore, the effect of urbanization was significantly strong and negative on the richness and diversity of beetles. Our results indicate that beetle communities are less rich and diverse in highly urbanized areas at both scales, which can lead to changes in community structure, ecological interactions and consequently threaten ecosystem services performed by this group.